(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The article examines data mining’s uses in manufacturing engineering, namely in the areas of Production processes, management, defect detection, maintenance, management assistance, and product quality improvement are all examples of what we do. In addition, customer service, data aggregation, and standards are addressed. briefly. Rather than addressing the data mining topic in general, this study focuses on showing the relevance of data mining to the manufacturing sector. Because of the large amount of general data mining literature, it’s difficult to obtain a clear picture of a target field like manufacturing engineering, which has its unique set of demands and requirements for mining applications. This examination shows forward-thinking applications, as well as current gaps and underserved sectors such as production planning and shop floor management.